2016
DOI: 10.1021/jacs.5b13533
|View full text |Cite
|
Sign up to set email alerts
|

Self-Exfoliated Guanidinium-Based Ionic Covalent Organic Nanosheets (iCONs)

Abstract: Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although π-π stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
358
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(389 citation statements)
references
References 55 publications
13
358
1
1
Order By: Relevance
“…Based on this strategy Banerjee et al synthesized ionic covalent organic nanosheets (iCONs) by reacting a planar C 3 symmetric cationic triaminoguanidinium halide TG X with 1,3,5-triformylphloroglucinol. 197 The obtained materials exhibited low crystallinity with a major broad peak at 2y = 27.31 indicating poor p-p stacking between the layers due to the loosely bound halogen anions and positive charge of the guanidinium units. Imidazolium ions are a class of organic cations very often found in ionic liquids, thus a rich chemistry is already reported on their chemical modification and functionalization.…”
Section: Cationic Microporous Polymersmentioning
confidence: 97%
“…Based on this strategy Banerjee et al synthesized ionic covalent organic nanosheets (iCONs) by reacting a planar C 3 symmetric cationic triaminoguanidinium halide TG X with 1,3,5-triformylphloroglucinol. 197 The obtained materials exhibited low crystallinity with a major broad peak at 2y = 27.31 indicating poor p-p stacking between the layers due to the loosely bound halogen anions and positive charge of the guanidinium units. Imidazolium ions are a class of organic cations very often found in ionic liquids, thus a rich chemistry is already reported on their chemical modification and functionalization.…”
Section: Cationic Microporous Polymersmentioning
confidence: 97%
“…Although numerous COF powder exfoliation methods have been reported, very few of these studies demonstrate the ability to reconstitute the resulting nanosheets into large‐area COF films . Most reported methods involve either sonicating the powders in organic solvents or mechanically grinding the powders prior to dispersion, but due to challenges with re‐aggregation and sedimentation at high concentrations, these strategies typically produce dilute suspensions (≤0.2 mg mL −1 ) that are not conducive to large‐scale film fabrication . Although Tsuru and co‐workers demonstrated that thin films can be prepared from a dilute suspension (0.15 mg mL −1 ) of COF‐1 powder prepared through sonication in dichloromethane, the fabrication process required repeated drop‐casting/drying cycles to form a continuous film, and therefore lacks scalability and practicality .…”
Section: Introductionmentioning
confidence: 99%
“…However, similarly to graphene, synthetic 2D organic frameworks are very difficult to process because of the great tendency of the individual layers to aggregate by noncovalent interlayer interactions. Although several examples of the delamination of 2D organic frameworks by mechanical9 and solvent‐assisted methods,10 electrostatic repulsion,11 and chemical methods12 have been reported, these methods provide materials that are a few layers thick and thereby show that the individualization of layers is still a challenging task.…”
mentioning
confidence: 99%